EVALUASI PROSEDUR DAN TEKNIS PENANGKARAN BENIH PADI DI DESA SENANING KECAMATAN PEMAYUNG KABUPATEN BATANG HARI - Fitriyani, Rissa; Murdy, Saad; Sativa, Fendria (Jurnal Ilmiah Sosio-Ekonomika Bisnis, 2019)
This research is aimed at: (1) Evaluating the level of performance and importance of procedure and technical of breeding of rice seed (2) Identifying the implementation of procedure and technical of breeding of rice seed. The study was conducted on September to October in deliberate deliberation (purposive) and the number of samples in the study were 33 farmers. The data used are primary and secondary data. Data analysis method used is descriptive analysis and IPA analysis method (importen perfomenc analysis). The results showed that the level of harmonious interests and performance: (a) land preparation of 98.5%, (b) maintenance of 96.88%, (c) 80.28% tile method, (d) harvest and seed processing 99.73% (e) 98.47% of storage means that in implementing the procedure and technical breeder of paddy seed attribute the level of its under 100% equity and attributes of which the level of the harmonious of interest and performance above 100% are: (f) sorting and (h) selection or roguing of 102.5%, observed variables (i) equal to 118.10%, and (j) packing 103.44% %. The interest-performance matrix classifies attributes into four quadrants, namely quadrant I, quadrant II, quadrant III and quadrant IV, attribute in quadrant II: (a) maintenance, (b) harvest (c) seed processing, attribute in quadrant III: ( d) sorting and seed treatment, (e) land preparation, (f) selection or roguing, (g) observed variables, (h) manner of tiling, (i) packaging and storage. The attribute yag is in quadrant IV: (j) planting.